High Diversity of Planctomycetes in Soils of Two Lichen-Dominated Sub-Arctic Ecosystems of Northwestern Siberia - Ivanova, Anastasia A.; Kulichevskaya, Irina S.; Merkel, Alexander Y.; Toshchakov, Stepan V.; Dedysh, Svetlana N. (Frontiers in Microbiology, 2016)
A wide variety of terrestrial ecosystems in tundra have a ground vegetation cover composed of reindeer lichens (genera Cladonia and Cetraria). The microbial communities of two lichen-dominated ecosystems typical of the sub-arctic zone of northwestern Siberia, that is a forested tundra soil and a shallow acidic peatland, were examined in our study. As revealed by molecular analyses, soil and peat layers just beneath the lichen cover were abundantly colonized by bacteria from the phylum Planctomycetes. Highest abundance of planctomycetes detected by fluorescence in situ hybridization was in the range 2.2-2.7×107 cells per gram of wet weight. 16S rRNA gene fragments from the Planctomycetes comprised 8-13% of total 16S rRNA gene reads retrieved using Illumina pair-end sequencing from the soil and peat samples. Lichen-associated assemblages of planctomycetes displayed unexpectedly high diversity, with a total of 89,662 reads representing 1723 operational taxonomic units determined at 97% sequence identity. The soil of forested tundra was dominated by uncultivated members of the family Planctomycetaceae (53-71% of total Planctomycetes-like reads), while sequences affiliated with the Phycisphaera-related group WD2101 (recently assigned to the order Tepidisphaerales) were most abundant in peat (28-51% of total reads). Representatives of the Isosphaera-Singulisphaera group (14-28% of total reads) and the lineages defined by the genera Gemmata (1-4%) and Planctopirus-Rubinisphaera (1-3%) were present in both habitats. Two strains of Singulisphaera-like bacteria were isolated from studied soil and peat samples. These planctomycetes displayed good tolerance of low temperatures (4-15°C) and were capable of growth on a number of polysaccharides, including lichenan, a characteristic component of lichen-derived phytomass.